Differential Effects of Device Modalities and Exposure to Online Reviews on Online Purchasing: A Field Study. Issue 4 (3rd August 2022) - Orimoloye, Larry Olanrewaju; Scheinbaum, Angeline Close; Kukar-Kinney, Monika; Ma, Tiejun; Sung, Ming-Chien; Johnson, Johnnie
Abstract: We model the effect of online information search across mobile (smartphone and tablet) and nonmobile (personal computer [PC], both desktop and laptop) platforms on frequency of purchasing per online shopping session. Using clickstream data from a multinational retailer, we find that device modality drives purchase frequency, likely due to the differential ease of use of PCs, tablets, and smartphones. In particular, frequency of completed orders is highest when information search and purchase completion are highly convenient, such as when shopping via tablet. We also determine that information search in the form of reading online product reviews has no effect on mobile platforms, while it does on other platforms. These findings contribute to information search theory, suggesting that information search increases purchase likelihood when it is goal directed, extensive, and easy to conduct. Thus, the broad role of digital advertising should be to make the information search process easier and more convenient for consumers to stimulate purchases. These findings help digital advertisers understand information search patterns across device modalities. Implications for digital advertisers on electronic commerce (e-commerce) platforms are offered.